To crowdfund research, scientists must build an audience for their work - Byrnes,Jarrett E; Ranganathan,Jai; Walker,Barbara L. E.; Faulkes,Zen (PeerJ PrePrints, 2014)
As rates of traditional sources of scientific funding decline, scientists have become increasingly interested in crowdfunding as a means of bringing in new money for research. In fields where crowdfunding has become a major venue for fundraising such as the arts and technology, building an audience for one’s work is key for successful crowdfunding. For science, to what extent does audience building, via engagement and outreach, increase a scientist’s abilities to bring in money via crowdfunding? Here we report on an analysis of the #SciFund Challenge, a crowdfunding experiment in which 159 scientists attempted to crowdfund their research. Using data gathered from a survey of participants, internet metrics, and logs of project donations, we find that public engagement is the key to crowdfunding success. Building an audience or “fanbase” and actively engaging with that audience as well as seeking to broaden the reach of one’s audience indirectly increases levels of funding. Audience size and effort interact to bring in more people to view a scientist’s project proposal, leading to funding. We discuss how projects capable of raising levels of funds commensurate with traditional funding agencies will need to incorporate direct involvement of the public with science. We suggest that if scientists and research institutions wish to tap this new source of funds, they will need to encourage and reward activities that allow scientists to engage with the public.
Keywords: crowdfunding; funding; science communication; science education; outreach; Twitter